PENGARUH PEMBERIAN PENUGASAN TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI SMA N 7 SIJUNJUNG - Limantori, Agus; Melia, Yenni; Yasin, Faisal (Pendidikan Sosiologi, 2014)
The begin from anyproblem where the writer observes at senior high school 7 sijunjung. One of the problemis about infience of the sociologi subject at senior high school 7 on XIÂ  grade in sijunjung is the teacher of sociology low in giving motivation to the students especity in giving the task. This research purposes to know how good studentâs motivation in doing the task in sociology learning at senior high school 7 on XI grade in sijunjung.Kind ofÂ  this research use quantitative approach the population is all the learners on XI grade of IPS 2013-2014 sample in taken by using proportional stratified random sampling research. Which is used in this research is quetionaise of the task and motivation.The result of this research shows that the research er found;Â  1) there is a significant infivence about thetask which is given by the teacher to the learning motivation, with Taccasut > table (11,240) 1,667). The power of relation include haed (r = 0,806) and big of the contribution infience about giving the task by teacher to the learning motivation is 65,0% . giving the task of the students can bee seen from guldeng or confrolling of the teacher. Given stimulation, guiding while the learner wants to work, or worked and notedbythe students itself without helving from the others this case means the task which is given by the teacher can improve students motivation.Â